Hegel's phenomenology of self-consciousness : text and commentary - Rauch, Leo (SUNY series in Hegelian studies., 1999)
"Offering a new translation of the famous chapter IV ("Self-Consciousness") of Phenomenology of Spirit, this book reflects the far-reaching insights of contemporary Hegelian scholarship. Included is extensive commentary as well as a review of its reception by such important twentieth-century thinkers as Kojeve, Heidegger, Sartre, Gadamer, Bataille, Deleuze, Lacan, and Habermas."--Jacket